EFEKTIVITAS PENERAPAN METODE DISKUSI-SIMULASI TERHADAP KETERAMPILAN MENGAJAR MAHASISWA CALON GURU BIOLOGI - Mufida Nofiana (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This research is a quasy experiment research that focus to identify an effectiveness of discussion-simulation methode to improve basic teaching skills of biology pre-teacher in University Muhammadiyah of Purwokerto. Data of this research colected by observation and evaluation, then analized by T-test and corelation with SPSS 16. The results are students improve their basic teaching skills after implementation this methode. T-test result for evaluation before implementation and after implementation methode is 0,00 and correlation between implementation methode and students basic teaching skills is 0,543. So, a discussion-simulation methode is effectives to improve basic teaching skills of biology pre-teacher in University Muhammadiyah Purwokerto. Keyword: a discussion-simulation methode, basic teaching skills